Renouer avec le vivant. De l'analyse réflexive d'une expérience de création vers une pédagogie artistique sensible dans une perspective énactive - Sylvie Morais (Université de Provence, 2021)
What can artistic education do in our context of ecological crisis that endangers future generations, the quality of our lives and that of the environment? To answer this "sensitive" question, we make the assumption, we need a pedagogy which reconnects with the living, an artistic pedagogy which seeks to re-establish the sensitive thread which connects living beings to the environment, to each other and to themselves. This article presents the reflexive analysis of our artistic creation research: Arborescence. Les verbes du vivant, an analysis which outlines the contours of a "sensitive" artistic pedagogy from an enactive perspective. The theory-in-action analysis of the creative experience is based on the dual professional practice of artist and teacher of the arts, and allows us to better understand how they enrich each other.